Análise da tectônica rúptil associada a uma porção do lineamento transbrasiliano da Região Noroeste do Ceará integrando dados de campo, magnetométricos e de sensoriamento remoto - Melo, Dayana Cristina Macedo de (2014)
The brittle tectonic analyzed in this work is referring to an area that represents a portion of the Transbrasiliano Lineament (TL), in northwest of Ceará State, comprising part of Cariré, Pacujá, Graça and Reriutaba’s county and the geological context is the basement (Ceará Complex-Canindé Unit) and Jaibaras and Parnaiba Basin (Jaibaras Group-Pacuja Formation and Serra Grande Group, respectively). This study aims to characterize the brittle structures associated to the TL, through integration of remote sensing (SRTM-Topodata and Landsat 7 ETM+), geophysics (Magnetometry) and field data information. From SRTM-Topodata images there were obtained drainage system and hillshade images in N, NE, E and NW directions. Color composition images RGB 743 and 431 derived from Landsat 7 ETM+. The combination of these products permitted the visualization of lineaments that were vectorized to compare to other data. The processed magnetometric data allowed to obtain the anomalous magnetic field and the elaboration of other products through application of variable filters, such as: horizontal and vertical Derived, analytic signal amplitude and analytic signal inclination. They were assets to identify lineaments and define magnetic domains. Anomalous magnetic their depth estimated by Euler deconvolution and matched filter application. The fracture planes’ rosette diagram elaborated from field measures composed parameters to compare the lineaments extracted from the products aforementioned. It’s evident, from the integration of all information, that the main direction of the TL (NE-SW) is compatible with the brittle structures observed in the area, as well as the N-S and NW-SE lineaments, that are potentially related with translative/extensional tectonic of TL. The E-W direction, which is late to TL and appears in the basement as the basins. The comparative analysis of the data suggests a tectonic control from TL over Jaibaras and Parnaiba Basins, through structures reactivation in NE and NW directions.